Seasonal training load distribution of professional futsal players: effects on physical fitness, muscle damage and hormonal status - Miloski, B.; de Freitas, V. H.; Nakamura, F. Y.; de A Nogueira, F. C.; Bara-Filho, M. G. (The Journal of Strength and Conditioning Research, 2016)
The aims of the present study were to describe the training load (TL) distribution of a professional futsal team and verify its subsequent effects on physical performance, muscle damage, and hormonal status. Twelve male professional futsal players (24.3 ± 4.7 years old; 75.5 ± 7.7 kg; and 173.4 ± 4.5 cm) participated in this study. A training program of 22 weeks (6 weeks of pre-season and 16 weeks of in-season) was analyzed. The session rating of perceived exertion method was used to monitor TLs. Physical tests (PTs; countermovement jump (CMJ), 5- and 20-m sprint, T-test, and multistage 20-m shuttle-run tests) were performed 4 times throughout the season (PT1-PT4). Blood sample (BS) collection (Creatine kinase [CK], testosterone, and cortisol) was performed in 7 occasions (BS1-BS7). TLs were higher in pre-season compared to in-season (p < 0.001). Countermovement jumps (CMJs) and 5- and 20-m performances were better in PT3 (CMJ: 0/23/77, 5-m: 0/3/97, and 20-m: 0/1/99) and PT4 (CMJ: 0/8/92, 5- and 20-m: 0/0/100) than in PT1; T-test performance and VO2max was better in all moments compared with those of PT1 (0/0/100). Higher CK concentration (p = 0.03) and testosterone to cortisol (T:C) ratio values (p = 0.02) were detected in BS2 vs. BS1. An increase in C (p = 0.007) and a decrease in T:C ratio (p = 0.003) was observed from BS4 to BS5. The training program demonstrated higher TLs during the periods with low incidence of matches, emphasis on endurance and strength training during pre-season, speed and power training throughout in-season. This TL organization provides sufficient stimulus for appropriate physical fitness development in professional futsal players, without causing negative disturbances.